Changing climate for populists? Examining the influence of radical-right political parties on low-carbon energy transitions in Western Europe. (August 2020) - Ćetković, Stefan; Hagemann, Christian
Abstract: Over the last two decades, populist radical-right parties (PRRPs) have been the most successful newcomers in European party systems. This article contributes to the emerging literature on populism and sustainability transitions by investigating the impact of PRRPs on energy and climate policy in six West European countries, Austria, Denmark, Finland, the Netherlands, Norway, and Sweden, in the period 2008-2018. The analysis shows that energy and climate policy efforts sometimes, but not always weaken when PRRPs participate in government or support minority governments. The negative policy influence of PRRPs has been most visible in cases where the domestic and international salience of the climate and energy issues was low and when PRRPs controlled relevant ministries. Interestingly, the article also finds that the rise of PRRPs has indirectly contributed to the improvements in low-carbon energy transition efforts in several countries by polarizing the political arena and strengthening the government influence of smaller progressive parties.